Investigating the role of de novo designed peptides in ameliorating amylin aggregation and β-cell toxicity in Type 2 Diabetes (T2D) - Gupta, Gaytri (2019)
Pancreatic β-cell dysfunction and apoptosis in Type 2 Diabetes (T2D) is associated with amylin aggregation and amyloid deposition. Current strategies targeting amyloidogenesis include the use of inhibitory peptides, segments of amylin sequence with “breaker elements”, to disrupt the aggregation process. However, no inhibitory molecules to date are in clinical use. In the present study, we: (i) compared amyloid deposition in pancreatic tissue collected from T2D patients and normal controls; (ii) modelled the amyloidogenic process of T2D ex situ, namely primary and secondary amylin nucleation aggregation; (iii) demonstrated aggregation toxicity in vitro in a pancreatic β-cell culture model; and (iv) tested the efficacy of two de novo designed peptides (CYI12 and LI12) in inhibiting amylin aggregation and ameliorating aggregation toxicity. LI12 did not have an inhibitory effect on aggregation, whereas CYI12 successfully inhibited both forms of primary and secondary nucleation aggregations. Surprisingly, CYI12 did not rescue cells from amylin aggregation toxicities in vitro. Instead, CYI12 potentially stabilised the toxic intermediates, demonstrated by a dose dependent decrease in cell viability. Based on the present work, CYI12 will be used as a starting point for sequence optimisation to produce a peptide that can both inhibit aggregation and rescue β-cell from associated toxicity.